Maslahat (Benefits) in Fiqh Awlāwiyāt: A Comparison between Yūsuf al-Qarādhawī’s View and Abdus Salam Alī al-Karbulī’s - Ifandy, Teguh; Hasanah, Idaul (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article examines and compares the concept of maslahat in the Fiqh Awlāwiyāt (fiqh of priority) in the view of Yūsuf al-Qarādhawī and Abdus Salam Alī al-Karbulī. The aim is to find similarities and differences between the two views. Fiqh Awlāwiyāt, which places maslahat as an important reference in determining the scale of priority, can be used to solve contemporary problems. Unfortunately, there are not many studies that discuss this in depth. This article is part of the results of normative legal research with a comparative approach. Data were collected through literature studies and analyzed using descriptive-comparative analysis techniques. This article finds similarities between Yūsuf al-Qarādhawī's thought and Abdus Salam Alī al-Karbulī's in determining the types and levels of maslahat needed in the scale of priority. In constructing Fiqh Awlāwiyāt, the two figures above are based on Fiqh Muwāzanāt. The difference in their thoughts lies in determining the scale of priority. Al-Qaradhawi uses the rules of fiqh, while al-Karbulī uses the al-Ta’ārudh method. However, the substance of their thoughts is similar and interrelated. Thus, it can be elaborated in the context of developing Fiqh Awlāwiyāt.